2021
DOI: 10.1007/s11356-021-15575-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of e-cigarettes on colonic mucosa and the role of recovery: involvement of oxidative and inflammatory pathway

Abstract: Electronic cigarettes (e-cigarettes) (EC) are often advertised as a safer alternative to conventional cigarettes. Its widespread use has led to increased interest in its adverse health effects, thanks to few restrictions and a lack of regulatory guidelines. The study aimed to evaluate the influence of exposure to e-cigarette aerosol inhalation in rat colon model and conduct a follow-up after cessation of exposure. The experiment included 30 male adult Albino rats. The animals were divided into three groups: gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…By contrast, in the colon, CS had no effect on apoptosis or cell proliferation, whereas both Mb18W and Mb30W e-cig exposure induced evident limitation of cell proliferation, demonstrated by histological crypt loss, epithelial surface decrease and a reduced number of proliferative cells in crypts. According to our results, a decrease in colon cell proliferation was reported in mice exposed to e-cig liquid vapor [ 24 ]. In contrast, to our knowledge, CS was reported as promoting or inhibiting colon cancer-cell proliferation [ 21 , 39 , 40 , 41 ], and its effect on normal colonic mucosa has never been studied before.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…By contrast, in the colon, CS had no effect on apoptosis or cell proliferation, whereas both Mb18W and Mb30W e-cig exposure induced evident limitation of cell proliferation, demonstrated by histological crypt loss, epithelial surface decrease and a reduced number of proliferative cells in crypts. According to our results, a decrease in colon cell proliferation was reported in mice exposed to e-cig liquid vapor [ 24 ]. In contrast, to our knowledge, CS was reported as promoting or inhibiting colon cancer-cell proliferation [ 21 , 39 , 40 , 41 ], and its effect on normal colonic mucosa has never been studied before.…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, an in vivo and ex vivo study reported that e-cig led to a compromised gut barrier and was associated with chronic gut inflammation [ 23 ]. In rats, e-cig exposure for 4 weeks induced oxidative stress, colonic mucosa epithelial loss, and inflammatory infiltration, as well as a decrease in goblet cells [ 24 ]. In mice, daily inhalation of mango-flavoured e-cig for one month was associated with colon inflammation [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, tobacco also has the effect of altering intestinal permeability and motility. 106 It is relatively complex to answer the question about the existence of a link between eating habits and IBD. Initially, it is necessary to distinguish between the impact of diet on the onset of the disease and the impact on the evolution and on the severity of the flare-up phases.…”
Section: Environmental Risk Factorsmentioning
confidence: 99%
“…However, the consensus on the effects of ENDS on oral health needs to be further strengthened ( 22 ). Studies have shown that these devices still have harmful effects on the respiratory ( 23 , 24 ), nervous ( 25 , 26 ), reproductive ( 27 , 28 ), and digestive systems ( 29 ), and they should be considered as carcinogenic factors due to their nicotine content and other additives ( 30 32 ). In spite of this, the risks of ENDS may also have been underestimated due to the vast amount of advertising claiming that ENDS pose less or no harm.…”
Section: Introductionmentioning
confidence: 99%